Nutzung von Verkehrsinformationsdiensten. Eine empirische Untersuchung des Routenwahlverhaltens am Beispiel BMW ASSIST. - Bogenberger, Klaus; Heucke, Alexa; Hass, Berthold H. (Deutscher Verkehrs-Verl., 2006)
Stau ist grundsätzlich eine sich selbst zerstörende Prognose. Denn je nachdem, welche Route die nachkommenden Fahrer wählen, kann ein Stau wachsen, sich auflösen oder sich verlagern. Für eine sinnvolle Kommunikation von Staumeldungen ist es daher wichtig, den Einfluss von Verkehrsinformationen auf das Routenwahlverhalten eines Fahrers möglichst genau abzuschätzen. difu

This paper focuses on the individual route choice behavior depending on traffic information that a driver receives from his individual traffic information service such as BMW ASSIST V-Info +. A research method using animated traffic scenarios was developed to put the test persons in hypothetical route choice situations where they had to make their personal route choice decision. Thereby it became very clear that there are two different user types of individual traffic information services. The "obedient" to which two third of the respondents belong tend to overreact and follow their traffic information service's recommendation right away and without hesitation. The last third however, the "critical", do not follow any route changing recommendations until they can confirm the congestion message with their own eyes. difu
Keywords: Öffentlicher Verkehr; Verkehrsplanung; Befragung; Verkehrsverhalten; Entscheidungsprozess; Information; Kommunikation; Verkehrsablauf; Verkehrsinformation; Stau; Verkehrsstau; Routenwahl; Verkehrsroute; Empirische Untersuchung; Verkehrsforschung